ASM Handbook. Volume 14A, (ASM International, 2005)
Volume 14A is the first of two volumes that covers the distinct processes and industries of bulk working and sheet forming. It provides comprehensive coverage and essential technical information on the process-design relationships that are needed to select and control metalworking operations that produce shapes from forging, extrusion, drawing and rolling operations. The volume discusses forming equipment, processes, materials, and advanced modeling techniques -- publisher.